Analisis Pengaruh Motivasi Kerja dan Training terhadap Produktivitas Kerja Karyawan Produksi pada PT. Bina Busana Internusa - Laksmi Sito Dwi Irvianti; Rizki Utami Poetri (Bina Nusantara University, 2012)
PT Bina Busana Internusa is a company engaged in garment, established since 1989, and has been widely recognized as one of the leading garment industry in Indonesia. The purpose of this study is to determine whether there is influence between working motivation and training on employee productivity partially and simultaneously. The method of analysis used in this study is the Pearson correlation, simple and multiple regressions. Data are obtained from the distribution of questionnaires to 92 production employees as respondents, and interviews with respondents and with the HRD PT Bina Busana Internusa as well. The questionnaire uses Likert scale which was to know the degree of disagreement and agreement from the employee to the statement on the questionnaire. The results in this study stated that motivation and training simultaneously have a significant impact on employee productivity. Working motivation has a relationship and partially affects employee productivity. So is the training has a relationship and partially affects employee productivity. Therefore, the expected results of this research may provide inputs for firms and employees in particular to increase the productivity.